2018
DOI: 10.1111/1475-6773.13072
|View full text |Cite
|
Sign up to set email alerts
|

Initiation of new psychotropic prescriptions without a psychiatric diagnosis among US adults: Rates, correlates, and national trends from 2006 to 2015

Abstract: Objectives To estimate rates and national trends of initiation of new psychotropic medications without a psychiatric diagnosis and to identify demographic and clinical correlates independently associated with such use among US adults in outpatient settings. Data Source Data were gathered from the 2006‐2015 National Ambulatory Medical Care Survey (NAMCS), a nationally representative sample of office‐based U.S. outpatient care. The sample was limited to adults aged 18 or older who received a new psychotropic dru… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
2

Relationship

2
8

Authors

Journals

citations
Cited by 21 publications
(9 citation statements)
references
References 27 publications
(85 reference statements)
0
9
0
Order By: Relevance
“…This study has several strengths. First, the nationwide population-based database provides prevalence of specific major psychiatric disorders diagnosed strictly by psychiatrists and reduces the bias regarding internal validity of psychiatric diagnosis between non-psychiatrists and psychiatrists [ 52 ]. Second, we expanded the spectrum of psychiatric disorders, including bipolar disorder and schizophrenia, and gave more comprehensive information of the differential outcome risks of each psychiatric disorder among patients with degenerative spine disease to fill the gap of previous studies in accordance with ageing population.…”
Section: Discussionmentioning
confidence: 99%
“…This study has several strengths. First, the nationwide population-based database provides prevalence of specific major psychiatric disorders diagnosed strictly by psychiatrists and reduces the bias regarding internal validity of psychiatric diagnosis between non-psychiatrists and psychiatrists [ 52 ]. Second, we expanded the spectrum of psychiatric disorders, including bipolar disorder and schizophrenia, and gave more comprehensive information of the differential outcome risks of each psychiatric disorder among patients with degenerative spine disease to fill the gap of previous studies in accordance with ageing population.…”
Section: Discussionmentioning
confidence: 99%
“…Antidepressants included monoamine oxidase (MAO) inhibitors, tricyclic antidepressants, selective serotonin reuptake inhibitors, serotonin-norepinephrine inhibitors, and "other" antidepressants (bupropion, mirtazapine, vilazodone, nefazodone, vortioxetine, and trazodone). We also analyzed trends in the use of benzodiazepines and stimulants (18)(19)(20) in visits for which bipolar disorder was listed among the primary diagnoses.…”
Section: Medication Classificationmentioning
confidence: 99%
“…These studies, however, did not examine community-based services, specifically, and most studies have focused on people with mild to moderate mental illness. For example, studies of the National Ambulatory Medical Care Survey found that treatment for depression tripled between 1987 and 1997 [ 61 ], and that most antidepressants are prescribed by primary care providers [ 62 , 63 ].…”
Section: Discussionmentioning
confidence: 99%